O uso da psicoeducação no cuidado da saúde mental de indivíduos com Neoplasia Endócrina Múltipla Tipo 1 familiar - Silva, Fellipe Sousa da (2024)
Introduction: Family syndromes affect approximately 8% of the world population, many of which are of genetic origin. The diagnosis of these syndromes can bring about not only physical but also emotional and psychological effects. Multiple Endocrine Neoplasia type 1 (MEN-1) is a genetic syndrome with autosomal dominant transmission, manifesting clinically mainly in the parathyroid, pancreas, and pituitary glands, impacting the quality of life of those affected. Psychoeducational interventions aim to work on coping mechanisms to understand and manage their condition, providing moments to better contemplate, feel, and act regarding their current issues, thus aiming for an improvement in both physical and mental health, promoting better adherence to treatment and greater autonomy concerning their health condition. Objective: To assess the use of psychoeducation as a coping resource for patients with familial endocrine neoplasia. Materials and Methods: A longitudinal, uncontrolled intervention study, before and after, approved by the institutional ethics committee (CAAE: 63465122.4.0000.5054), was conducted on individuals with MEN-1 undergoing tertiary care. Study participants underwent evaluation through questionnaires before and after psychoeducational interventions. The interventions occurred after the interview and questionnaire application, with an average time of 50 minutes overall, utilizing the time to reflect on their health aspects and social atom usage. Validated questionnaires assessing anxiety and depression (HAD), Distress Management - Thermometer and Problem List - NCCN, and the Coping Strategies Inventory (EMEP) were used, and RedCap® was employed for data recording and collection. Variables were analyzed using the Shapiro-Wilk test. Pearson and Fischer's tests, Student's t-test, or Mann-Whitney tests were utilized where appropriate, adopting a significance level of 5%. Analysis were performed using RStudio® software. Results: The sample comprised 60 participants with a confirmed diagnosis of MEN-1, encompassing 14 identified families, 55% women, 43% in the age range of 36 - 50 years, 52% partnered, 52% with a high school education, living with an average income of 1 to 3 minimum wages (71%). Anxiety factors were present in 63%, which decreased to 30% after interventions (score ≥8), while depressive factors were observed in 43%, reducing to 20% after interventions (score ≥9). The Distress Thermometer measured an average of 6.25±2.74, indicating a high level of distress (>4). The results highlighted that the most frequently utilized coping strategies were problem-focused coping (78%) and religious practices (77%), while the less frequently utilized ones were emotion-focused coping (46%) and seeking social support (56%). It was observed that after the psychoeducational interventions, there was a reduction in the HAD scale scores from 9.5±5.2 to 6.2±4.3 in anxiety factors and from 7.8±4.3 to 5.0±4.0 in depressive factors (N=60). Regarding the Distress Thermometer, there was a decrease from 6.25±2.74 to 4.98±2.52 (N=60) following the interventions. Conclusion: Psychoeducational interventions prove to be an important ally in the process and support of patients affected by familial syndromes, allowing individuals to take ownership of their realities and exercise spontaneity in their lives, i.e., the ability to give new responses to what has been happening to them. The results show an improvement and reduction in anxiety, depression, and individual distress, thereby enhancing their quality of life.